The obstacles to teaching English for the secondary stage in the Education Directorate in the Aqaba Governorate from the viewpoint of the subject teachers - Almousah, Maryam Hammad Abdallah (Journal of Educational and Psychological Sciences, 2020)
The aim of the present study was to uncover obstacles of teaching English at the secondary level in the Directorate of Education in the Aqaba Governorate from the point of view of the subject’s teachers. To achieve the goals of the study, the researcher used the descriptive approach. The study tool was a questionnaire distributed to a sample of (65) teachers, who represent (81%) of the study population. Using the statistical program (spss), the results of the study showed that the total degree of obstacles has obtained a total average of (4.242), and at the level of the two axes: the axis of administrative obstacles got a mean average of 4.43) followed by the technical obstacles axis, with an average of (4.055) and all of them with a degree (High). The results showed that there are statistically significant differences between the views of male and female teachers in technical and administrative obstacles. In light of the results, a number of recommendations and proposals were presented to overcome the obstacles facing instructors of English language teaching at the Directorate of Education in the Aqaba Governorate, and all the directorates of Jordan.